2001
DOI: 10.1002/neu.1042
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the central generator of locomotor rhythm by noncompetitive NMDA receptor antagonists in Drosophila larvae

Abstract: The noncompetitive antagonists of the vertebrate N-methyl-D-aspartate (NMDA) receptor dizocilpine (MK 801) and phencyclidine (PCP), delivered in food, were found to induce a marked and reversible inhibition of locomotor activity in Drosophila melanogaster larvae. To determine the site of action of these antagonists, we used an in vitro preparation of the Drosophila third-instar larva, preserving the central nervous system and segmental nerves with their connections to muscle fibers of the body wall. Intracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
92
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 58 publications
(54 reference statements)
12
92
0
Order By: Relevance
“…As noted above, AMPA-like receptors have already been implicated since KaiRIA (brec) mutants are paralyzed and have reduced SRC frequency (Featherstone et al, 2005). In addition, noncompetitive NMDA receptor antagonists have also been shown to inhibit rhythmic locomotor activity in larvae (Cattaert and Birman, 2001), but the role of these NMDA-like receptors in CNS motor circuitry remains to be tested by genetic means. The metabotropic glutamate receptor mGluRA is unlikely to be involved since null mutants are viable and have only mild defects of synaptic plasticity and morphology at neuromuscular syn- apses (Parmentier et al, 1996;Ramaekers et al, 2001;Bogdanik et al, 2004;Devaud et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…As noted above, AMPA-like receptors have already been implicated since KaiRIA (brec) mutants are paralyzed and have reduced SRC frequency (Featherstone et al, 2005). In addition, noncompetitive NMDA receptor antagonists have also been shown to inhibit rhythmic locomotor activity in larvae (Cattaert and Birman, 2001), but the role of these NMDA-like receptors in CNS motor circuitry remains to be tested by genetic means. The metabotropic glutamate receptor mGluRA is unlikely to be involved since null mutants are viable and have only mild defects of synaptic plasticity and morphology at neuromuscular syn- apses (Parmentier et al, 1996;Ramaekers et al, 2001;Bogdanik et al, 2004;Devaud et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…We found that glutamate receptors become sufficiently desensitized, at millimolar concentrations of LGA (Ն5 mM), to allow 80 Hz stimulation of the nerve without muscle contraction (0.5 or 2 mM [Ca 2ϩ ] o ). Stimulation trains of 80 pulses at 80 Hz were chosen to test the Ca 2ϩ handling properties of MN terminals during activity because this paradigm resembles MN activity during fictive locomotion (Cattaert and Birman, 2001;Barclay et al, 2002). We examined the amplitude of OGB-1 fluorescence transients evoked during 10 Hz stimulation in shi MN terminals in the presence of 7 mM LGA and found no difference (paired t test; p ϭ 0.78) relative to the amplitude of transients in its absence (⌬F/F R of 28.2 Ϯ 8.5% with and 29.3 Ϯ 6.3% without; n ϭ 5).…”
Section: Methodsmentioning
confidence: 99%
“…Larval crawling, used for travel across various types of terrain, is accomplished by repeated peristaltic wave-like strides (8) and involves molecules mediating neuronal signaling (9)(10)(11)(12). Whereas one study suggests that embryonic assembly of CPG for larval locomotion does not require sensory inputs, the same study reports that interference with the sensory function during embryogenesis severely disrupts the actual patterns of locomotion (13).…”
mentioning
confidence: 99%